Praça Roosevelt: ocupação e transformação do espaço público (1967-2018) - Azevedo, Carlos Roberto de (2018)
The present study aims to analyze aspects of the building, implantation, occupation, and consequent transformation of the Roosevelt Square (Praça Roosevelt, located in the central region of São Paulo) from 1967 to 2018. This analysis will firstly include a presentation of its four most relevant projects: the first and second of 1967; the third of 2008; and the fourth and last of 2010 – the last two being re-qualification projects. In the 2010 project, we will analyze morphological issues of the architecture based on authors such as Francis D.K. Ching (2013) and Geoffrey H. Baker (1998), and qualitative or humanistic issues, based on the author Jean Gehl (2015). The analysis takes into account how the population appropriated and currently makes use of this public space, which contrasts with the occupation originally designed for the area. In the current occupation of the Square, we can highlight its use as space for skateboarding and for cultural manifestations, such as theater performances. In summary, this work consists of the description of the urban insertion of Roosevelt Square from the metropolitan scale to the local scale, the presentation of the detailed history of the Square and its four major projects conceived from 1967, as well as the analysis of the 2010 project – effectively implemented and currently in use. This analysis aims to examine the morphological, qualitative and humanistic aspects of this project and seeks to emphasize the importance of taking these issues into account for the design of a public space.